A preliminary study of thermosphere and mesosphere wind observed by Fabry‐Perot over Kelan, China. Issue 6 (16th June 2014) - Yu, Tao; Huang, Cong; Zhao, Guangxin; Mao, Tian; Wang, Yungang; Zeng, Zhongcao; Wang, Jingsong; Xia, Chunliang
Abstract A Fabry‐Perot interferometer (FPI) system was deployed in Kelan (38.7°N, 111.6°E), center China in November 2011, which observes the airglows at wavelengths of 892.0 nm, 557.7 nm, and 630.0 nm from OH and OI emissions in the upper atmosphere, to derive the wind and temperature at heights around 87 km, 97 km, and 250 km, respectively. From late 2011 through 2013 a series of more than 4500 measurements at each height are validated according to manufacture data quality criteria. By using these data, the morphology of wind in the mesosphere and thermosphere is investigated in this study. Preliminary results are as follows: (1) As for the diurnal variation, meridional and zonal winds at heights of 87 km and 97 km, which are derived through 892.0 nm and 557.7 nm airglows, usually range from −50 m/s to 30 m/s and −50 m/s to 50 m/s, respectively, with typical random errors of about 6–10 m/s at 87 km and 2–3 m/s at 97 km. Meridional winds usually are northward at dusk, southward at middle night, and back to northward at dawn; and zonal winds usually are eastward at dusk, westward at middle night, and back to eastward at dawn. The monthly mean winds are in good agreement with those of HWM93 results. Meridional and zonal winds at a height of 250 km, which are derived through 630.0 nm nightglow, range from −110 m/s to 80 m/s with typical random errors of about 8–10 m/s. Meridional winds usually are northward at dusk, southward at middle night, and back to northward at dawn; and zonal winds usually are eastward at dusk, zero at middle night, and westward at dawn; and they are also well consistent with HWM93 results. (2) As for the seasonal variation, meridional winds at the heights of 87 km and 97 km have a visible annual variation at 12–17 LT and with a little semiannual variation at all other hours, but the zonal winds at the heights of 87 km and 97 km have a semiannual variation all night. The seasonal dependence of the winds, both meridional and zonal winds, at the height of 250 km is generally annual, but isolated cases of semiannual variation are observed. (3) The horizontal winds at 250 km evidently respond to the two storms of July 2012, apparent enhancement of the velocity of the southwestward wind. But no other obvious storm effects can be found from the winds at 87 km and 97 km during the same period.